Analisis Faktor-Faktor yang Memengaruhi Minat Petani dalam Penggunaan Bibit Dengan Media Soil block pada Budidaya Cabai (Capsicum Frutescens L.) - Latyfatusstany, Sylmy; Sujono, Sujono; Ismarlin, Ina Fitria (Jurnal Agroteknologi (Agronu), 2025)
Increasing the productivity of cayenne pepper is the main focus in the horticulture sub-sector to meet the increasing market demand. Intensification of cayenne pepper cultivation has an impact on increasing plastic waste from the use of conventional seeds such as trays and polybags. As a solution, seeds with soil block media are introduced as an environmentally friendly seedling innovation that does not produce plastic waste and is of high quality. This study aims to analyze the effect of age variables, education level, land area, length of farming, role of extension workers, role of groups and infrastructure on the interest (feeling of pleasure, attention, awareness and willingness) of farmers in using seeds with soil block media in chili (Capsicum frutescens L.) cultivation. The study was conducted in Tirtomartani Village, Kalasan District, Sleman Regency in November 2024 - March 2025. The method used is quantitative descriptive with multiple linear regression analysis techniques. Data were obtained through observation, interviews, and questionnaires from 60 respondents selected using proportional random sampling techniques. The results of the analysis showed that simultaneously all X variables had a significant effect on farmers' interest in using seeds with soil block media. However, in terms of infrastructure, only facilities and infrastructure showed a significant influence. Therefore, there needs to be a follow-up in the form of empowering farmer groups in the form of optimizing the use of seeds with soil block media as an effort to improve farmers' knowledge, attitudes and skills in using seeds with soil block media